KAJIAN HUKUM AGRARIA TENTANG PENATAAN BATAS TANAH UNTUK MENINGKATKAN KEPASTIAN HUKUM HAK MILIK DI KABUPATEN SERANG - Gilang Ramadhan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Land boundary arrangement is a crucial issue in agrarian law because it is directly related to legal certainty of land ownership. In Serang Regency, land disputes still occur due to unclear boundaries, overlapping rights, and procedural obstacles. This study aims to analyze the legal basis for land boundary arrangement in Indonesia and Serang Regency, identify legal and procedural obstacles, and evaluate the role of clear land boundaries in enhancing legal certainty of land ownership. This research uses a qualitative normative legal research method with secondary data, including legal documents, regulations, agrarian law books, journal articles, and official documents from the Serang BPN. The findings show that the legal basis for land boundary arrangement is available through the Basic Agrarian Law (UUPA), Government Regulation No. 24 of 1997, Minister of ATR/BPN Regulations, regional regulations, and court decisions, yet its implementation faces legal, procedural, and cultural challenges. Clear land boundary arrangements can enhance legal certainty of ownership, prevent land disputes, and support transparency and accountability in land administration. The study recommends strengthening inter-agency coordination and integrating formal law with customary land rights to achieve effective legal certainty